A review on the role of IoT, ai, and blockchain in agriculture & crop diseases detection using a text mining approach - Puri, Bhuvan; Cambow, Rameshwar (Ingeniería Solidaria, 2023)
Introduction: This paper is the outcome of a review survey, “Role of IoT, AI and blockchain in agriculture and crop disease detection using a text mining approach,” done at Lovely Professional University in Punjab, India, in 2023.Problem: Agriculture is a crucial industry that contributes significantly to the economies of many nations. Crop diseases are one of the issues that create a barrier to agricultural development.Objective: Using machine learning, deep learning, image processing methods, the Internet of Things, and blockchain technology, this study provides a current summary of research done over the past years on disease identification of various crops.Methodology: The text mining technique is applied to extract the related information from published papers and predict the following futuristic technologies to detect crop diseases early.Results: This paper also covers the various issues, challenges, and potential solutions. It also emphasizes the wide range of tools available for identifying crop diseases.Conclusion: This paper helps to extract valuable keywords through a text-mining approach and create a roadmap for another researcher.Originality: Applied text mining visualization techniques, such as word cloud and word frequency, to extract the keywords.Limitation: The literature survey only covers literature published prior to February 2023; it can be extended withmore studies published soon.
Keywords: IoT; AI; crop diseases; agriculture; text mining; blockchain